2018
DOI: 10.1177/1759720x18785539
|View full text |Cite
|
Sign up to set email alerts
|

Improving drug adherence in osteoporosis: an update on more recent studies

Abstract: Similar to other chronic diseases such as diabetes and hypertension, osteoporosis has struggled with suboptimal medication adherence, resulting in an increased risk of fractures and all-cause mortality. The goal of this narrative review was to summarize interventions to improve medication adherence in osteoporosis. Because past reviews of this topic covered published literature through 2013, we conducted our literature search to include the period between January 2012 and November 2017. We identified 10 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Data suggest that Fracture Liaison Services, and pharmacist-delivered counselling, may have positive influences on adherence to recommended osteoporosis medications44; this is imperative, given that non-adherence to osteoporosis medications has been associated with increased fracture risk over 12 months of follow-up 45. However, the reduced 10-year fracture probability that we observed suggests that interventions other than osteoporosis medication may have a positive effect on fracture risk, particularly given the suggestion that only 4%–30% of reduced fracture risk in association with antiresorptive therapy can be attributed to changes in BMD 46.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that Fracture Liaison Services, and pharmacist-delivered counselling, may have positive influences on adherence to recommended osteoporosis medications44; this is imperative, given that non-adherence to osteoporosis medications has been associated with increased fracture risk over 12 months of follow-up 45. However, the reduced 10-year fracture probability that we observed suggests that interventions other than osteoporosis medication may have a positive effect on fracture risk, particularly given the suggestion that only 4%–30% of reduced fracture risk in association with antiresorptive therapy can be attributed to changes in BMD 46.…”
Section: Discussionmentioning
confidence: 99%
“…With the progressive aging of the general population, osteoporosis has emerged as a medical and socioeconomic problem. However, most current treatment options for osteoporosis have limitations and side effects that affect their long-term administration and patient adherence ( Rachner et al, 2011 ; Jaleel et al, 2018 ). Disturbance of osteoblast or osteoclast regulation would also lead to abnormal accumulation of bone, such as osteosclerosis, which is classified according to its causative factor as either acquired or hereditary.…”
Section: Introductionmentioning
confidence: 99%
“…The VA’s specific guidance for osteoporosis recommends that for low adherence (<80%) to oral bisphosphonates to “institute local measures to improve adherence” after 2 years 5 ; however, reliable methods to improve adherence are lacking. 4…”
Section: Discussionmentioning
confidence: 99%
“…A review of published interventions to promote adherence to osteoporosis treatment found many interventions were not effective and the ones that reported improved adherence were expensive and/or lower quality studies. 4 With this in mind, low-adherence patients should be considered for osteoporosis therapies that are known to have better adherence, including denosumab 29 and zoledronic acid. 30 This is especially relevant for high fracture risks patients such as those with baseline fracture or tobacco users.…”
Section: Discussionmentioning
confidence: 99%